Nutrient enrichment and rainfall affect plant phenology and floral resource availability for pollinators - Thuma, Jessie A.; Duff, Christopher; Pitera, Madeline; Januario, Nicholas; Orians, Colin M.; Starks, Philip T. (Frontiers in Ecology and Evolution, 2023)
Wild pollinators are critical to maintaining ecosystem services and facilitating crop production, but habitat degradation and resource loss are leading to worldwide pollinator declines. Nutrient enrichment and changes in rainfall due to global warming are drivers of global environmental change, and likely to impact pollinator foraging behavior and reproductive success through changes to the growth and phenology of flowering plants. Here, we provide a short review of pollinator conservation in the context of nutritional ecology and plant-pollinator interactions. Then, we present novel research into the effects of nutrient and rainfall variation on plant phenology. In this study, we experimentally manipulated the amount of water and supplemental nutrients available to wild sunflower (Helianthus annuus) and goldenrod (Solidago sp.) throughout their growing season. We evaluated how changes in growth and bloom time could impact resource availability for bumble bee (Bombus impatiens) queens preparing to overwinter. We found that fertilizer and rainfall alter plant bloom time by 2-18 days, though flowering response was species-specific. Fertilizer did not significantly affect plant growth or number of flowers produced when plants were grown under drought conditions. When water was not limiting, fertilized sunflowers bloomed in floral pulses. These findings carry important implications for growers and land managers, providing insight into potential drivers of wild pollinator decline and possible conservation strategies.